Analysis Of Factors Affecting White Chili Production (Case Study on Coffee Plantations in Kembang Seri Village, Bermani Ilir District, Kepahiang Regency) - Anisa Septi Liani; Eddy Silamat; Anadiya Pingki; Mira Yanuari (International Journal of Education, Vocational and Social Science, 2025)
This study was conducted in February 2025 to March 2025. This study aims to analyze the factors that influence the production of white cayenne pepper in Kembang Seri Village, Bermani Ilir District, Kepahiang Regency. The sampling technique used in this study is theSnowball sampling It is known that the respondents used were 25 people, where the respondents were farmers who planted white cayenne pepper under coffee trees in Kembang Seri Village, Bermani Ilir District. The data analysis method in this study was AnalysisCobb douglass a function or equation involving two or more dependent variables that are explained (Y), and the other is called the independent variable (X). The results of this study indicate that the production factors that affect the production of white cayenne pepper at a confidence level of 95% (0.05) are land area, number of seeds, amount of organic fertilizer, amount of inorganic fertilizer, and amount of pesticides while the number of workers does not affect the production of white cayenne pepper because the results of the labor analysis have a t-value smaller than the t table (0.718 <1.714). Therefore, the number of workers does not significantly affect the production of white cayenne pepper in Kembang Seri Village, Bermani Ilir District, Kepahiang Regency.